The use of phase change material as an actuator in linkage fabric structures - Partik, Christian; Porte, Elze; Purkiss, Danielle; Michalska, Martyna; Miodownik, Mark (Frontiers in Materials, 2023)
Linkage fabric structures show potential as assistive technology that can provide support and assistance for individuals with specific mobility and disability needs. The core functionality of these fabrics is the ability to passively and actively control the mechanics of each link producing a structure with variable and adjustable stiffness. Current actuators have shown limited ability to produce active stiffening within a fabric structure without the addition of a continuous energy supply to the structure, therefore, limiting its use as wearable assistive technology. Here, we address the energy supply problem and show the novel use of sodium acetate trihydrate (SAT) in the linkage structures to induce mechanical stiffening through a phase change induced by an electric impulse. We find that a SAT aqueous concentration of 55 wt% is optimum to achieve a stable supercooled liquid (to ambient temperature) and effective electrical nucleation from liquid to solid, which provides robust locking mechanism of individual linkages able to withstand mechanical torsion up to 200mNm. We demonstrate proof of principle through the integration of SAT into one-and twodimensional linkage structures and their nearly instantaneous stiffening within each link by enabling electrically controlled actuation.